Kualitas hidup dengan kualitas tidur remaja SMA Katolik Rex Mundi Manado di masa pandemi COVID-19 - Paskah Thalia Lengkong; Frelly Kuhon; Windy M. V. Wariki (UNIVERSITAS SAM RATULANGI, 2022)
The COVID-19 pandemic is causing anxiety in the community. This anxiety is also felt by adolescents so teenagers become one of the groups at risk of having poor sleep quality. Unmet sleep quality may have an impact on improving health for the process of restoring body functions in order to complete daily tasks and have a good quality of life. This research aims to describe the quality of life along with the quality of sleep of Catholic High School teenager Rex Mundi Manado during the COVID-19 pandemic. This was a descriptive study with a cross-sectional design. Students of Rex Mundi Catholic High School who reach the inclusion criteria were recruited through cluster random sampling. WHOQOL-BREF and PSQI questionnaires were used as tools through online data collection In total,. 87 students participated in this study and showed the average quality of life score in the physical domain, psychology, social relations, and the environment was at a score of 51-75. The majority of students had scores good enough for subjective sleep quality, 1-2 for latent sleep, 6-7 hours of sleep, efficient sleep >85%, sleep disorder scores of 1-9, and the majority had never used sleep medications in the past month, and for daytime dysfunction had a score of 1-2. The conclusion of the study is that most respondents have a moderate level of quality of life in the domain of physical, psychological, social relationships, environment, and have good sleep quality.Keywords: quality of life, quality of sleepÂ